Research on the Thermal Runaway Behavior and Flammability Limits of Sodium-Ion and Lithium-Ion Batteries - Changbao Qi; Hewu Wang; Minghai Li; Cheng Li; Yalun Li; Chao Shi; Ningning Wei; Yan Wang; Huipeng Zhang (Batteries)
Batteries are widely used in energy storage systems (ESS), and thermal runaway in different types of batteries presents varying safety risks. Therefore, comparative research on the thermal runaway behaviors of various batteries is essential. This study investigates the thermal runaway characteristics of sodium-ion batteries (NIBs), lithium iron phosphate batteries (LFP), and lithium-ion batteries with NCM523 and NCM622 cathodes. The experiments were conducted in a nitrogen-filled constant-volume sealed chamber. The results show that the critical surface temperatures at the time of thermal runaway are as follows: LFP (346 °C) > NIBs (292 °C) > NCM523 (290 °C) > NCM622 (281 °C), with LFP batteries exhibiting the highest thermal runaway critical temperature. NIBs have the lowest thermal runaway triggering energy (158 kJ), while LFP has the highest (592.8 kJ). During the thermal runaway of all four battery types, the primary gases produced include carbon dioxide, hydrogen, carbon monoxide, methane, ethylene, propylene, and ethane. For NCM622 and NCM523, carbon monoxide is the dominant combustible gas, with volume fractions of 35% and 29%, respectively. In contrast, hydrogen is the main flammable gas for LFP and NIBs, with volume fractions of 44% and 30%, respectively. Among these, NIBs have the lowest lower flammability limit (LFL), indicating the highest explosion risk. The thermal runaway characteristics of 50 Ah batteries provide valuable insights for battery selection and design in energy storage applications.